Effect of companion presence on maternal satisfaction during neuraxial catheter placement for labor analgesia: a randomized clinical trial. (May 2019) - Morell, E.; Peralta, F.M.; Higgins, N.; Suchar, A.; Fitzgerald, P.; McCarthy, R.J.
Highlights: Satisfaction during epidural placement was enhanced when a companion was in the room. Companion presence did not affect maternal anxiety. Companion presence did not affect the procedure time. Companion presence during catheter placement should be considered a positive option. Abstract: Background: Neuraxial labor analgesia is frequently achieved after placing an epidural catheter under sterile conditions. There is no consensus on the risk versus benefit of allowing a parturient's companion to remain during the procedure. We sought to assess the effect of the presence of a companion on maternal satisfaction and anxiety during neuraxial catheter placement for labor analgesia. Methods: Healthy nulliparous parturients planning to receive neuraxial labor analgesia after admission to labor, and who had a companion with them at the time of interview, were randomized to having a companion present or not present in the labor and delivery room during neuraxial catheter placement. Participants completed questionnaires to assess maternal anxiety, pain catastrophizing and health literacy. Satisfaction was scored on 5-point Likert scale (1- highly dissatisfied, 2- dissatisfied, 3- neutral, 4- satisfied, 5- highly satisfied). Results: A total of 143 participants completed the study. The Wilcoxon–Mann–Whitney odds ratio for a random pair of satisfaction scores for a woman with her companion present compared with companion not present was 1.93 (95% CI 1.30 to 2.81, P =0.001). Anxiety scores were decreased following the procedure ( P =0.39) in both groups. Eighty-nine percent of women randomized to companion not present would have preferred to have a companion present ( P  <0.001) compared with only one with their companion present who would have preferred her companion to be not present ( P =0.99). Conclusion: Maternal satisfaction can be improved with the presence of a companion in the labor and delivery room at the time of neuraxial catheter placement for labor analgesia.